Sharp Lipschitz Constants for the Distance Ratio Metric - Simić, Slavko; Vuorinen, Matti; Wang, Gendi (MATHEMATICA SCANDINAVICA, 2015)
We study expansion/contraction properties of some common classes of mappings of the Euclidean space R^n, n2, with respect to the distance ratio metric. The first main case is the behavior of Möbius transformations of the unit ball in R^n onto itself. In the second main case we study the polynomials of the unit disk onto a subdomain of the complex plane. In both cases sharp Lipschitz constants are obtained.